Low Radiation Environment Switches the Overgrowth-Induced Cell Apoptosis Toward Autophagy - Fischietti, Mariafausta; Fratini, Emiliano; Verzella, Daniela; Vecchiotti, Davide; Capece, Daria; Di Francesco, Barbara; Esposito, Giuseppe; Balata, Marco; Ioannuci, Luca; Sykes, Pamela; Satta, Luigi; Zazzeroni, Francesca; et al. (Frontiers in Public Health, 2021)
Low radiation doses can affect and modulate cell responses to various stress stimuli, resulting in perturbations leading to resistance or sensitivity to damage. To explore possible mechanisms taking place at an environmental radiation exposure, we set-up twin biological models, one growing in a low radiation environment (LRE) laboratory at the Gran Sasso National Laboratory, and one growing in a reference radiation environment (RRE) laboratory at the Italian National Health Institute (Istituto Superiore di Sanità, ISS). Studies were performed on pKZ1 A11 mouse hybridoma cells, which are derived from the pKZ1 transgenic mouse model used to study the effects of low dose radiation, and focused on the analysis of cellular/molecular end-points, such as proliferation and expression of key proteins involved in stress response, apoptosis, and autophagy. Cells cultured up to 4 weeks in LRE showed no significant differences in proliferation rate compared to cells cultured in RRE. However, caspase-3 activation and PARP1 cleavage were observed in cells entering to an overgrowth state in RRE, indicating a triggering of apoptosis due to growth-stress conditions. Notably, in LRE conditions, cells responded to growth stress by switching toward autophagy. Interestingly, autophagic signaling induced by overgrowth in LRE correlated with activation of p53. Finally, the gamma component of environmental radiation did not significantly influence these biological responses since cells grown in LRE either in incubators with or without an iron shield did not modify their responses. Overall, in vitro data presented here suggest the hypothesis that environmental radiation contributes to the development and maintenance of balance and defense response in organisms.